Structure activity optimization of 6H-pyrrolo[2, 3-e][1, 2, 4]triazolo[4, 3-a]pyrazines as Jak1 kinase inhibitors. Issue 20 (15th October 2015) - Friedman, Michael; Frank, Kristine E.; Aguirre, Ana; Argiriadi, Maria A.; Davis, Heather; Edmunds, Jeremy J.; George, Dawn M.; George, Jonathan S.; Goedken, Eric; Fiamengo, Bryan; Hyland, Deborah; Li, Bin; et al.
Graphical abstract